Pengaruh Edukasi terhadap Pengetahuan dan Sikap tentang Konsumsi Jajanan Sehat pada Siswa Kelas 4 SDN Merjosari 2 Kota Malang - Jihan Aliyah; Moh. Zainol Rachman; Dimas Dwi Yoga (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Introduction: Health issues resulting from unhealthy snacks remain common among elementary school children in Indonesia. In 2023, the National Agency of Drug and Food Control (BPOM) recorded 1,110 cases of food poisoning, with East Java ranked second. Screening conducted in 2024 at elementary schools under the Dinoyo Community Health Center revealed 66 cases of diarrhea in Lowokwaru District. Research Purposes: This study aimed to determine the effect of educational intervention on the knowledge and attitudes toward healthy snack consumption among 4th-grade students at SDN Merjosari 2, Malang City. Method: This research employed a pre-experimental design with a one-group pretest-posttest approach. The population and sample included all 29 fourth-grade students, selected through total sampling. Data were analyzed using the Wilcoxon signed-rank test. Results: Findings indicated an improvement in knowledge and attitudes after the intervention. Students with good knowledge increased from 7% to 41%, while those with poor knowledge decreased from 55% to 14%. Positive attitudes rose from 55% to 69%. Wilcoxon test results showed p-values of 0.01 for knowledge and 0.00 for attitude, both below the significance level of 0.05, indicating a statistically significant effect. Conclusion: Educational intervention had a significant influence on the knowledge and attitudes of fourth-grade students at SDN Merjosari 2 regarding healthy snack consumption.